Immunological Memory to Zika Virus in a University Community in Colombia, South America - CÁRDENAS, DENNY M.; JAIMES, MIGUEL A.; VEGA, LEIDY D.; OLIVEROS, NICOLAS L.; SOTO, JAVIER A.; CHÍA, CLAUDIA R.; OSORIO, JORGE E.; CIUODERIS, KARL A. (Anais da Academia Brasileira de Ciências, 2020)
Zika virus appeared in South America in 2015, generating alarm worldwide as it causes microcephaly and autoimmunity. This study aims to determine the serological footprint of the incoming epidemic in a student community and to characterize the memory functional cell response during post convalescence. In a cross-sectional study, Zika-specific IgG using LIA immunoassay was found in 328 university students (CI=95%), while in the second phase, the functional cellular memory response for IFN-γ and IL-2 was quantified using post-stimulus ELISpot with inactivated virus, starting with individuals seropositive for Zika and control individuals (seropositive only for Dengue and seronegative for Zika-Dengue). Depending on the antigen used, memory humoral response (IgG) against Zika Virus was observed in >60% of the population; seropositivity for NS1 was 21.1% higher than E antigen with high intensity. The analysis of cell functionality in 22 individuals seropositive for Zika virus revealed either IFN-γ+ or IL-2+ cells in 86.3% of cases (Th1 profile), presenting multifunctionality in 50% (11 individuals), 64% of which presented> 6 SFC/104 PBMCs (>600 SFC/106 PBMC), reflecting memory circulating cells. A good agreement (Kappa= 0.754) was observed between the coexistence of both cellular and humoral responses but not in their intensity.Zika virus appeared in South America in 2015, generating alarm worldwide as it causes microcephaly and autoimmunity. This study aims to determine the serological footprint of the incoming epidemic in a student community and to characterize the memory functional cell response during post convalescence. In a cross-sectional study, Zika-specific IgG using LIA immunoassay was found in 328 university students (CI=95%), while in the second phase, the functional cellular memory response for IFN-γ and IL-2 was quantified using post-stimulus ELISpot with inactivated virus, starting with individuals seropositive for Zika and control individuals (seropositive only for Dengue and seronegative for Zika-Dengue). Depending on the antigen used, memory humoral response (IgG) against Zika Virus was observed in >60% of the population; seropositivity for NS1 was 21.1% higher than E antigen with high intensity. The analysis of cell functionality in 22 individuals seropositive for Zika virus revealed either IFN-γ+ or IL-2+ cells in 86.3% of cases (Th1 profile), presenting multifunctionality in 50% (11 individuals), 64% of which presented> 6 SFC/104 PBMCs (>600 SFC/106 PBMC), reflecting memory circulating cells. A good agreement (Kappa= 0.754) was observed between the coexistence of both cellular and humoral responses but not in their intensity.